2016
DOI: 10.3892/ijmm.2016.2576
|View full text |Cite
|
Sign up to set email alerts
|

A potential role for zinc transporter 7 in testosterone synthesis in mouse Leydig tumor cells

Abstract: Abstract. Previous studies have demonstrated that zinc (Zn) is an essential trace element which is involved in male reproduction. The zinc transporter (ZnT) family, SLC30a, is involved in the maintenance of Zn homeostasis and in mediating intracellular signaling events; however, relatively little is known regarding the effect of ZnTs on testosterone synthesis. Thus, in the present study, we aimed to determine the effect of Zn transporter 7 (ZnT7) on testosterone synthesis in male CD-1 mice and mouse Leydig cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 47 publications
(63 reference statements)
0
23
0
Order By: Relevance
“…Therefore, supporting our results, coadministration of ZnO-NPs and THO synergistically increase the testosterone concentration rather than each alone. Two pathways could explain our findings; (a) testosterone synthesis from cholesterol induced by THO [20], or (a) endogenous molecular factors in the Leydig cells stimulated by the ZnO-NPs which require additional research and molecular studies [54]. The same pathway explains the increased secretion and volume of seminal plasma from the accessory genital glands which mainly depend on the testosterone secretion [56].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Therefore, supporting our results, coadministration of ZnO-NPs and THO synergistically increase the testosterone concentration rather than each alone. Two pathways could explain our findings; (a) testosterone synthesis from cholesterol induced by THO [20], or (a) endogenous molecular factors in the Leydig cells stimulated by the ZnO-NPs which require additional research and molecular studies [54]. The same pathway explains the increased secretion and volume of seminal plasma from the accessory genital glands which mainly depend on the testosterone secretion [56].…”
Section: Discussionmentioning
confidence: 81%
“…Accordingly, the blood cholesterol could be directed for the production of testosterone in agreement with our findings. Moreover, Zn concentrations in the Leydig cells were found to be significantly lowered in mice fed a Zn-deficient diet compared to controls, and that the zinc transporter-7 (ZnT7) was principally expressed in the Leydig cells ZnT7 which plays an important role in the regulation of testosterone synthesis by modulating the steroidogenic enzymes [54]. All above suggests that zinc could play a direct pivotal role on those testosterone-secreting cells which coincide with our findings for the highest increment of testosterone in response to ZnO-NPs supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Chu et al . [2] study on Leydig cells in mice found that Zn transporters (ZnT7) may play an important role in the regulation of testosterone synthesis by modulating steroidogenic (STARs) enzymes and may represent as therapeutic target in testosterone deficiency. In singing birds, testosterone levels influence the quality of sound and feathers.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc is also drawn in lipid catabolism which is the energy source for sperm to actively motile. In addition, zinc is also associated with testosterone secretion, so that it's undoubtedly required in male reproduction (Chu et al, 2016). The activity of ribonuclease enzyme also demanded zinc existence to process spermatogenesis, during spermatogenesis, and at the end of spermatogenesis (Widhyari et al, 2015).…”
Section: Discussionmentioning
confidence: 99%